Galantamine administration reduces reactive astrogliosis and upregulates the anti‐oxidant enzyme catalase in rats submitted to neonatal hypoxia ischemia. Issue 62 (29th July 2017) - Odorcyk, F.K.; Nicola, F.; Duran‐Carabali, L.E.; Figueiró, F.; Kolling, J.; Vizuete, A.; Konrath, E.L.; Gonçalves, C.A.; Wyse, A.T.S.; Netto, C.A.
Abstract: Neonatal hypoxia ischemia (HI) plays a role in the etiology of several neurological pathologies and causes severe sequelae. Acetylcholine is a neurotransmitter in the central nervous system and cholinesterase inhibitors have demonstrated a positive action over HI induced deficits. In order to evaluate the effects of pre and post‐hypoxia administrations of galantamine, a cholinesterase inhibitor, in a model of perinatal HI, Wistar rats in the post‐natal day 7 (PND7) were subjected to a combination of unilateral occlusion of the right carotid artery with the exposure to a 1 h hypoxia. Intraperitoneal injections of galantamine were administered in two different protocols: one pre and other post‐hypoxia. The analysis of brain structures volume at PND45 showed that pre‐hypoxia galantamine treatment prevented tissue injury to the ipsilesional hippocampus. Also, immunofluorescence showed HI‐induced increase in the number of astrocytes that was prevented by pre‐hypoxia treatment. Biochemical analysis was performed in the ipsilesional hippocampus at PND8 and revealed that pre‐hypoxia galantamine treatment: 1) prevented the neuronal loss induced by HI; 2) reduced the HI‐induced hypertrophy of astrocytes; and 3) caused an increase in the activity of the anti‐oxidant enzyme catalase. Overall, treatment with galantamine was able to prevent the brain damage, increase the survival of neurons, reduce astrocytic reaction and increase the activity of the anti‐oxidant enzyme catalase in rats submitted to neonatal hypoxia ischemia.